Charles Armitage Brown, John Keats and Plymouth*. (3rd July 2017) - Roe, Nicholas
Abstract: This article explores Charles Armitage Brown's residence at Laira, Plymouth, 1835–41. His cottage at Laira survives and is explored, as are Brown's activities at the Plymouth Institution. His friendship with Keats is discussed, and his publication of some fifteen of Keats's poems in Plymouth newspapers, The Plymouth, Devonport and Stonehouse News and The Plymouth and Devonport Weekly Journal . The purpose of the article is to draw attention to Brown's Keats-related activities at Plymouth as a significant stage in the development of the poet's reputation.